The lonely path of migrant women in Greece - Maratou-Alipranti, Laura; Fakiolas, Rossetos (The Greek Review of Social Research, 2003)
About 330,000 foreign immigrant women, out of a total foreign immigrant population close to one million persons, have resided in Greece since the mid-1990s. These women are characterized by diverse patterns of motivation for entering Greece, legal status, ethnicity, migration type (i.e., independent versus associational, transient versus permanent), kinds of employment and living conditions. The overwhelming majority are economic migrants who entered the country illegally or legally but work without permits. After the two legalisations in 1998 and 2001 most of them have acquired a legal status. They show however a high propensity to lapse again into illegality by not renewing their permits, while new illegal arrivals pour in. About two thirds of the women, the same as the male migrants come from Albania and a further 6% from Bulgaria, both bordering Greece. A total of about 86% of female migrants come from the former socialist countries of Eastern Europe, including those of the former Soviet Union. The remaining come from dozens of other source countries in all continents. They represent every religion, with Christians of various denominations and Moslems topping the list. Their motivations range from supporting financially their families at home or in Greece (the considerable number of migrant pupils has been on the increase), to advancing their careers, acquiring more work experience, and combining tourism with employment. Hardly any are illiterate and about one in six or seven have tertiary education. A considerable proportion migrate alone as independent migrants, following a lonely path by striving on their own to settle and make a living in a foreign country. Although there are indications that an increasing number intend to remain in Greece for many years, the majority appear to be transient migrants, not intending permanent settlement. Their living conditions are highly diverse.